Development of a sensitive real-time PCR for simultaneous detection and subtyping of influenza A and B viruses (Italian Journal of Public Health, 2005)
A new real-time PCR assay, using melting curve analysis, was developed for the rapid and reliable detectionand sub-typing of influenza A and B. In order to evaluate it’s specificity, cell culture surnatants positive forRespiratory Syncytial Virus, Parainfluenza Viruses 1, 2 and 3, Measles Virus, Influenza A (to evaluateInfluenza B primer) and B (to evaluate Influenza A primer) were tested and all of the results were negative.A series of Influenza A and B cell culture-grown viruses were diluted in virus transport medium, titrated andtested to determine the analytical sensibility which equated to 0.64, 0.026, 0.64, 0.62 PFU for A/H1N1,A/H3N2, Victoria-like and Yamagata-like B viruses, respectively. Twenty-five specimens, collected during the2001/02 and 2002/03 seasons, which were positive for A/H1N1 (n = 7), A/H3N2 (n = 10), B Victoria-lineage(n = 5) and B Yamagata-lineage (n = 3), were tested in order to evaluate the assay’s clinical sensitivity, all ofthe results were positive. The new real-time PCR appears to be a suitable tool for virological surveillance andthe diagnosis of respiratory infections
Keywords: influenza viruses; real-time; virological surveillance